Performance Characteristics of UV and Visible Spectrophotometry Methods for Quantitative Determination of Norfloxacin in Tablets (Journal of Scientific Research, 2014)
This work has proposed the development and validation of ultraviolet (UV) and visible (Vis) spectrophotometric methods for the determination of norfloxacin in the tablets. The proposed methods were applied to pharmaceutical formulation and percent amount of drug estimated (96.08% for UV method and 102.65% for Vis method) and was found in good agreement with the label claim. Using the UV method norfloxacin showed an absorption maximum at 277 nm, in 0.1 M hydrochloridric acid medium, whereas for the Vis spectrophotometric method it reacts with chloranilic acid reagent, forming a purple solution with an absorption maximum at 520 nm. The calibrations curves were linear over the working range of 2.0-7.0 ?g.mL-1 for the UV method and 90.0-120.0 ?g/mL for the Vis method. The linear regression equation for UV method was y = 0.1303x+0.0026 (r2=0.9999) and for Vis method y = 0.0037x-0.0069 (r2 = 0.9948), they proved to be linear. The methods were completely validated according to the International Conference Harmonization (ICH) guidelines, showing good accuracy, precision, selectivity, linearity and robustness. Therefore the both methods were found to be simple, rapid, sensitive, and easily contributing to the quality control of norfloxacin tablets while being interchangeable. © 2014 JSR Publications. ISSN: 2070-0237 (Print); 2070-0245 (Online). All rights reserved. doi: http://dx.doi.org/10.3329/jsr.v6i3.18381 J. Sci. Res. 6 (3), 531-541 (2014)